Malignant potential in pancreatic neoplasm; new insights provided by circulating miR-223 in plasma. (June 2015) - Komatsu, Shuhei; Ichikawa, Daisuke; Miyamae, Mahito; Kawaguchi, Tsutomu; Morimura, Ryo; Hirajima, Shoji; Okajima, Wataru; Ohashi, Takuma; Imamura, Taisuke; Konishi, Hirotaka; Shiozaki, Atsushi; Ikoma, Hisashi; et al.
<x xml:space="preserve">Abstract</x> Background: Recent studies have identified that microRNAs are stably detectable in plasma/serum because of their binding to specific proteins or being packaged in secretory vesicles. Methods: We tested miR-223 as a candidate of novel plasma biomarker in pancreatic cancer (PCa) and intraductal papillary mucinous neoplasm (IPMN). Results: i) miR-223 expression was significantly higher in PCa tissues (p = 0.0069) than in normal tissues. ii) Plasma miR-223 levels were significantly higher in 71 PCa patients than 67 healthy volunteers (p < 0.0001). iii) Plasma miR-223 levels were significantly reduced in postoperative samples (p = 0.0297). iv) Plasma miR-223 levels tended to discriminate the malignant potential between benign IPMN and malignant IPMN (p = 0.0963), and the progressive extent of invasiveness between malignant IPMN and pancreatic invasive ductal carcinoma (PIDC) (p = 0.0004). Multivariate logistic regression analysis revealed that a low level of plasma miR-223 was an independent risk factor for PIDC (p = 0.0012, odds ratio 7.90 [95% CI: 2.06 – 41.2]). v) There was no significant correlation between plasma miR-223 levels and the number of any blood cell types in the peripheral blood. Conclusion: Plasma miR-223 might be a clinically useful biomarker for screening PCa, and predicting malignant potential of IPMN and the invasiveness of PCa.